Empowerment of caregivers and families in making the elderly 'SEBASIS'; healthy free of tuberculosis - Farsida, Farsida; Larasati, Rahma Ayu; Darisan, Kemalasari Nas; Herdiansyah, Dadang; Utami, Ikrimah Nisa; Setyawati, Katharina (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Tuberculosis (TB) is an infectious disease that is still a public health problem, and one of the biggest causes of death in Indonesia. According to BPS, the number of elderly people in 2022 is around 30 million people and in 2050 will increase by 74 million people. This demographic shift shows that the elderly are an age group that deserves attention, especially in terms of Health. The impact of the Covid 19 pandemic coupled with decreased endurance and lung capacity that is not optimal, can cause the elderly to be susceptible to tuberculosis. The team of lecturers and students of FKK UMJ seeks to prevent tuberculosis by providing special education for elderly companions or caregivers at the Tresna Werdha Budi Mulya 1 social institution in East Jakarta. The event includes pre-test, education on the prevention and diagnosis of tuberculosis in the elderly, and post-test. T test results obtained p-value of 0.000, with an increase in the average knowledge after education of 6.72. It can be stated that educational activities for caregivers provide a significant increase in knowledge.